Negotiating the Needs and Readiness of Pondok Warga Emas as an Islamic Tourism Destination in Malaysia - Rafida A. R, Norhayati; W., Norailis, A.; M., Siti Zubaidah; A, Norfaizah Nadhrah; Y, Noor Azrina (International Journal of Psychosocial Rehabilitation, 2020)
Since 1985, Malaysia has become a popular tourist destination and experienced consistent annual growth in foreign tourist. In parallel with the growth of Islamic tourism destinations, this study views Pondok Warga Emas (senior homes) (PWE) as a business opportunity for Islamic tourism in Malaysia. PWE has been increasing in number and demand, which leads to the question: to what extent can PWE become an Islamic tourism destination in Malaysia? What are the potential needs and readiness level of PWE? This study thus identifies the needs and assesses the readiness of PWE as an Islamic tourism destination in Malaysia. A qualitative approach is employed and data are obtained through in-depth interviews with the management of PWE and travel agencies that are randomly chosen from Selangor, Kelantan, Kedah, Johor and Perak. The collected information is analyzed using content and framing analysis. The needs are found to be emphasized on shariah compliance, tour packages and Islamic tourism itself, while the readiness refers to the content, fees, authority/monitoring and use of social media for marketing purposes. A further examination is suggested to include foreign tourists and publics on the potential marketability of PWE as an Islamic tourism destination in Malaysia.